Immunological aspects of tear fluid - Mrugacz, Małgorzata; Żywalewska, Nella; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The eye is linked to the common mucosal immune system. This system play the part in preservation of the ocular surface. Tear fluid contains pro and anty-inflammatory factors such as lactoferrin, plasmin, immunoglobulins, and a lot of cytokines (interleukins, GM-CSF, TGF alfa and beta). The cornea is immunologicaly preferred, as a result of lack of resident lymphoreticular cells.